TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION: AN EFFECTIVE THERAPY TO WOMEN FOR PAIN MANAGEMENT AFTER VAGINAL DELIVERY - Fatima, Nisar; Rasheed, Ayesha; Shoukat, Ilza; Quraishi, Amna; Babar, Iza; Hussain, Asma (Annals of Allied Health Sciences, 2022)
Objective: To determine the effectiveness of Transcutaneous Electrical Nerve Stimulation for pain control after vaginal delivery. Material & Methods: It was a single blind experimental design carried out at different hospitals of Gujarat city including from February to April 2017. A total of sixty healthy females who delivered via vaginal route were randomly assigned with the help of coin tossing to the placebo group (sham intervention) and the experimental group (TENS group). To compare both the groups at the end of treatment, independent t-test was applied. Results The mean age of females in experimental and sham therapy groups were 31.54 ± 3.74 years and 33.42 ± 3.52 years, respectively. There was no differences when patients in both groups were compared. However, significant differences were observed when both the groups were compared on frequency of taking analgesics. In experimental group, there was no need of taking analgesics by 19 females, 5 females needed single dose and only 2 females needed double dose of analgesics. In control group 3 females needed no analgesics, 12 females needed single dose and 9 females needed double dosage of analgesics. Conclusion: The effects of TENS on pain reduction following vaginal delivery are promising and it can decrease the frequency of taking analgesics.